2019
DOI: 10.3168/jds.2018-14967
|View full text |Cite
|
Sign up to set email alerts
|

Production of recycled manure solids for use as bedding in Canadian dairy farms: II. Composting methods

Abstract: Recent technological advances in the dairy industry have enabled Canadian farms with liquid manure systems to use mechanical solid-liquid separation paired with composting of the separated solids for on-farm production of low-cost bedding material. However, because several approaches are available, it is difficult for farmers to select the appropriate one to achieve high quality recycled manure solids (RMS). Whereas 3 solidliquid manure separators were compared in part I of the series (companion paper in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The low DM content of RMS produced with the screw press used in this study may limit direct use of the RMS without further processing. Consequently, part II of the series (Fournel et al, 2019) compares composting methods as subsequent treatment for the production of high quality RMS.…”
Section: Discussionmentioning
confidence: 99%
“…The low DM content of RMS produced with the screw press used in this study may limit direct use of the RMS without further processing. Consequently, part II of the series (Fournel et al, 2019) compares composting methods as subsequent treatment for the production of high quality RMS.…”
Section: Discussionmentioning
confidence: 99%
“…1, all mixes showed a thermophilic stage at the beginning of the process, reaching 55-64 °C. In the study by Fournel et al (2019), with temperatures from 45 to 65 °C, they were effective in the reduction of bacterial growth. In a study conducted by Lafond et al (2002) it was observed that pathogen survival was closely related to the C/N ratio.…”
Section: Microbial Populationsmentioning
confidence: 99%
“…In general, the foreign researchers believe this practice to have several significant advantages: lower economic expenditures on bedding purchase and transportation, lower external supply dependency, weaker stresses associated with the housing systems and improved livestock health [10,12,32,33].…”
Section: International Experiencementioning
confidence: 99%
“…It is used in North America and Europe. In Russia, however, it is only starting to be introduced [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%